287. Development of a supervision model for women at high-risk (personal or family) of breast cancer based on Contrast-Enhanced Spectral Mammography. Cost/benefit ratio evaluation and optimization of a new alternative diagnostic path with respect to the traditional ones. (December 2018) - La Forgia, D.; Didonna, V.; Basile, T.; Bellotti, R.; Carbonara, R.; Losurdo, R.L.; Moschetta, M.; Tamborra, P.; Tangarop, S.; Fanizzi, A.; Massafra, R.
Abstract : Purpose: Dual-energy contrast-enhanced spectral mammography (CESM) has emerged as a potential new option for breast cancer staging. This imaging technique allows acquisition of multiple views of both breasts after a single injection of iodinated Contrast Medium (CM). It based on the fact that the CM injected will have different uptake path between hypervascularized breast lesions and background parenchyma. The aim of this paper is to evaluate the performance of identifying and characterizing the breast lesions, costs and comfort of patients of a supervision CESM single-step path with respect to a traditional double-step path mammography and MRI. Methods: We collected data on 46 patients who performed CESM: we have selected a subsample that also performed mammography in tomosynthesis and MRI. A total of 33 lesions have been identified by histological examination (28 malignant and 5 benign). The findings of all the techniques have been submitted to double blind check by two radiologists. The test was performed on 2D synthetic images of tomosynthesis and confirmed in low-energy images of CESM as reported in literature[1] . We have performed a statistical analysis of the diagnostic performances of each method in order to estimate the efficiency of the proposed diagnostic path with the only CESM technique with respect to the traditional path. Results: This study have shown consistent results in terms of sensitivity (over 90%) and between paths. The total costs of CESM alone were lower than the combination of digital mammography and MRI with CM, and between the different methods, while the greater discomfort was reported by patients undergoing MRI. Conclusions: The comparison between the methods has underlined the validity of the CESM supervision model both as morphological examination with respect to traditional mammography, and as dynamic examination with respect to MRI, according to the literature. In addition, CESM is more tolerated by patients than MRI and less expensive than the traditional paths.